Starlink dan Tata Kelola Ruang Antariksa: Analisis Hukum Internasional terhadap Dual-Use dan Dominasi Orbit - Damaris Septyana; Abyan Azhale Azhari; Mohammad Ichwanul Hakim; Raflah Dzaki Alwassi; Sarah Novianti (Sanskara Hukum dan HAM, 2025)
The development of SpaceX's Starlink mega satellite constellation has created significant changes in modern space governance and challenged the effectiveness of the international legal framework, which still relies on the 1967 Outer Space Treaty. With thousands of satellites operating in low Earth orbit, Starlink contributes to orbital congestion, global access inequality, and the strategic dependence of countries on private communications infrastructure. This study analyzes how Starlink's expansion has direct implications for the fundamental principles of space law. First, the principle of non-appropriation is threatened by Starlink's de facto dominance of orbital slots and frequency spectrum, which has the potential to transform space from a global commons into an arena of corporate control. Second, the principle of peaceful use faces challenges due to Starlink's dual-use nature in military operations, as seen in Ukraine, blurring the line between civilian and military use and potentially making commercial satellites targets of conflict. Third, the principle of state responsibility becomes problematic when the launching state, in this case the United States, legally bears international responsibility for SpaceX's activities, while operational decisions that have geopolitical implications are in the hands of corporations. The findings of this study confirm the existence of a law lag between the development of satellite technology and the legal framework that regulates it, and demonstrate the urgency of establishing new legal instruments that are capable of regulating private mega-constellations in a clearer, fairer, and more sustainable manner. Thus, this descriptive study using normative legal methods analyzed qualitatively contributes to the discussion on space governance reform in an era dominated by non-state actors.